Pengaruh Pemasaran Sosial Media Dan E-Wom Terhadap Niat Beli Konsumen Pada Grab-Food di Kota Medan - John Fedrick Louis Saragih; Hilma Harmen; Riris Amigo Simatupang; Gaby Putri Fenita Tampubolon; Indah Monalis (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to analyze the influence of marketing via social media and Electronic Word of Mouth (E-WOM) on consumer purchase intentions for Grab-Food services in Medan City. The research design used was quantitative, with a purposive sampling technique involving 100 respondents who were active users of social media and Grab-Food services in Medan City. Data was collected through a questionnaire using a 5 point Likert scale and analyzed using statistical methods. The research results show that social media has an influence on consumer purchasing intentions, but this influence is not partially significant with a significance value of 0.061 > 0.05. On the other hand, E-WOM has a significant influence on consumer purchase intentions with t count 6.743 > t table 2.052. Joint analysis between social media and E-WOM shows that these two variables simultaneously have a significant effect on consumer purchase intentions, with an F test value of Fcount 57.135 > Ftable 3.091.